Gibbon songs and intergroup dynamics: a community-level network analysis - Luca Morino; Andrew J J MacIntosh (Revue de Primatologie)
Most recent studies of hylobatid populations underline the flexibility of their 'nuclear groups' and recommend adopting a broader perspective, one that takes into account interactions across the whole community. Nevertheless, to date no such attempt has been reported. We used data on singing and agonistic interactions among 7 groups of wild siamangs to build the first community-level network for a hylobatid (or a primate) species. We show how such perspective can allow the identification of biologically relevant patterns and the testing of predictions about various open questions in gibbon socioecology, such as the function of singing, the mechanisms of group formation and the trade-offs existing both within and between one-male and two-males groups.